Surface Structure Engineering of Nanosheet-Assembled NiFe2O4 Fluffy Flowers for Gas Sensing - Xiaofeng Wang; Xu Li; Guozheng Zhang; Zihao Wang; Xue-Zhi Song; Zhenquan Tan (Nanomaterials, 2021)
In this work, we present a strategy to improve the gas-sensing performance of NiFe2O4 via a controllable annealing Ni/Fe precursor to fluffy NiFe2O4 nanosheet flowers. X-ray diffraction (XRD), a scanning electron microscope (SEM), nitrogen adsorption–desorption measurements and X-ray photoelectron spectroscopy (XPS) were used to characterize the crystal structure, morphology, specific surface area and surface structure. The gas-sensing performance was tested and the results demonstrate that the response was strongly influenced by the specific surface area and surface structure. The resultant NiFe2O4 nanosheet flowers with a heating rate of 8 °C min−1, which have a fluffier morphology and more oxygen vacancies in the surface, exhibited enhanced response and shortened response time toward ethanol. The easy approach facilitates the mass production of gas sensors based on bimetallic ferrites with high sensing performance via controlling the morphology and surface structure.